Migration and Diaspora Formation New Perspectives on a Global History of Christianity - Burlăcioiu, Ciprian (Arbeiten zur Kirchengeschichte, 2022)
Migration has come to be regarded as one of the defining features - if not the feature - of our times. Church History as an academic discipline has so far paid only limited attention to this changing reality. What would a global history of Christianity look like if it were to pay attention the way people's religion was influenced by experiences of disruption like migration and the conditions of diaspora?